Association between response to the medical treatment and predicting factors in ectopic pregnancy - Shahgheibi, Sholeh; Nasrollazadeh, Saman; Soufizadeh, Nasrin; Naghshbandi, Mobin (Chronic Diseases Journal, 2018)
BACKGROUND: Ectopic pregnancy (EP) is the leading cause of maternal death in the first trimester of pregnancy. There are many variables which can predispose EP. The aim of this study was to evaluate the possible association between individual’s response to given medical treatment and predicting factors of ectopic pregnancy among pregnant women. METHODS: In this cross-sectional study, 277 patients with ectopic pregnancy who were admitted to obstetrics and gynecology ward of Besat hospital, Sanandaj, Iran, were evaluated. The necessary information was obtained from all women diagnosed with EP during 2008 to 2013. Patients who received any medication before study or those who could not use methotrexate (MTX) were excluded from study. RESULTS: In this study, 205 (74.1%) patients responded to the medical therapy. There was a significant association between successful response to the treatment and beta human chorionic gonadotropin (β-hCG) serum level less than 5000 mIU/ml, pregnancy sac size less than 4 cm and lack of fetal heart rate (FHR) in transvaginal sonography (TVS). CONCLUSION: In conclusion, it was found that β-hCG serum level, pregnancy sac size and presence of FHR play a key role in predicting the response to the medical treatment in women with ectopic pregnancy, and might be helpful in selecting appropriate therapeutic scheme.